1998
DOI: 10.1177/096032719801700310
|View full text |Cite
|
Sign up to set email alerts
|

Acute paraquat poisoning: increased toxicity in one case with high alcohol intake

Abstract: Human paraquat poisoning from accidental or intentional ingestion is very often fatal. According to the amount of paraquat involved, death can occur within hours or weeks following ingestion. The inefficacy of the various treatments undertaken have led to determine prognostic factors based upon the evolution of plasma and urine paraquat concentrations or of usual biochemical parameters. We report one case of acute poisoning which, although the ingested dose of paraquat was not massive (550 mg/kg Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…12 It has long been known that paraquat increases the ratio of oxidised glutathione to glutathione in the liver and this deranged ratio can be detected in the plasma. 13 Alcoholic patients also lack adequate levels of protective intracellular glutathione 14 and, indeed, N-acetyl cysteine has been used experimentally in an attempt to prevent paraquat damage following ingestion. 15 In the lung, capillary endothelial and type I epithelial cells are both affected in the early stages before the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has long been known that paraquat increases the ratio of oxidised glutathione to glutathione in the liver and this deranged ratio can be detected in the plasma. 13 Alcoholic patients also lack adequate levels of protective intracellular glutathione 14 and, indeed, N-acetyl cysteine has been used experimentally in an attempt to prevent paraquat damage following ingestion. 15 In the lung, capillary endothelial and type I epithelial cells are both affected in the early stages before the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other toxic effects of paraquat include ventricular arrhythmias, hypotension and cardio-respiratory arrest. The toxicity of paraquat may be enhanced by concomitant alcohol intake 11 because animal studies showed ethanol increased the intestinal absorption and tissue distribution of paraquat. The critical fatal plasma concentration of paraquat was lower in the presence of ethanol because of the increased volume of distribution.…”
Section: Clinical Featuresmentioning
confidence: 99%